Role of molecular markers to predict distant metastasis in papillary thyroid carcinoma: Promising value of TERT promoter mutations and insignificant role of BRAF mutations—a meta-analysis. Issue 10 (October 2017) - Vuong, Huy Gia; Altibi, Ahmed MA; Duong, Uyen NP; Ngo, Hanh TT; Pham, Thong Quang; Tran, Hung Minh; Oishi, Naoki; Mochizuki, Kunio; Nakazawa, Tadao; Hassell, Lewis; Katoh, Ryohei; Kondo, Tetsuo
The presence of distant metastasis is associated with an adverse outcome in papillary thyroid cancer. We performed a meta-analysis to investigate the role of molecular markers as predictors for distant metastasis in papillary thyroid cancer. Four electronic databases including PubMed, Web of Science, Scopus, and Virtual Health Library were searched, and odds ratio and its 95% confidence interval concerning the association of BRAF, RAS, and TERT promoter mutations and RET/PTC rearrangements with distant metastasis were calculated using random-effects model. In total, 42 studies with 11, 109 papillary thyroid cancers were included for meta-analyses. Overall, the presence of TERT promoter (odds ratio = 5.95; 95% confidence interval = 2.95–11.99), RAS mutations (odds ratio = 2.5; 95% confidence interval = 1.00–6.22), and RET/PTC rearrangements (odds ratio = 1.92; 95% confidence interval = 1.03–3.56) were found to be associated with a significantly increased risk for distant metastasis. BRAF mutations were not associated with an elevated risk for distant metastasis (odds ratio = 0.79; 95% confidence interval = 0.54–1.16). In conclusion, our study demonstrated the promising value of few molecular biomarkers, especially TERT promoter mutations in predicting distant metastasis in papillary thyroid cancers, while BRAF mutations showed no association with distant metastasis. Our study affirms the value of selected mutations for tumor risk stratification and assessment of patients' prognosis.